2006 IEEE 4th World Conference on Photovoltaic Energy Conference 2006
DOI: 10.1109/wcpec.2006.279907
|View full text |Cite
|
Sign up to set email alerts
|

Performance Measurements of CIS Modules: Outdoor and Pulsed Simulator Comparison for Power and Energy Rating

Abstract: A method for energy yield prediction under development in this laboratory has proved to be accurate for crystalline Si modules, however, in the determination of an energy rating of CIS modules, it was found to be difficult to accurately predict the module performance based on simulator measurements. The Energy Rating (ENRA) procedure is based on determining the maximum power point Pmax as a function of the irradiance and the module temperature using standard pulsed simulator measurements. Long term outdoor mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…The crystalline modules are therefore stable for the purpose of comparing measurements possibly taken over the medium term from different measurement systems. However, it is well known that thin film modules typically demonstrate instabilities and performance changes depending on their history of exposure to light and temperature fluctuations [15][16][17]. This can make comparison of the results measured at different times in Power rating of photovoltaic modules to implement IEC 61853-1 R. P. Kenny et al…”
Section: Test Modules and Reference Devicesmentioning
confidence: 99%
“…The crystalline modules are therefore stable for the purpose of comparing measurements possibly taken over the medium term from different measurement systems. However, it is well known that thin film modules typically demonstrate instabilities and performance changes depending on their history of exposure to light and temperature fluctuations [15][16][17]. This can make comparison of the results measured at different times in Power rating of photovoltaic modules to implement IEC 61853-1 R. P. Kenny et al…”
Section: Test Modules and Reference Devicesmentioning
confidence: 99%
“…Material related effects are mainly due to LS 6, 14, 15 and can significantly influence the performance of TF devices at standard test conditions (STC) depending on their recent history (exposure to light or storage in the dark).…”
Section: Source Of Measurements Errorsmentioning
confidence: 99%
“…As shown in Refs. 6, 14 some CIS devices are highly sensitive to LS effects, whereas others are less so. In some cases, even the exposure to light for fractions of second – what we call the pre‐measurement state 6 – can alter a device's response.…”
Section: Source Of Measurements Errorsmentioning
confidence: 99%
“…Copper–indium sulfide (CIS) and copper–indium–gallium selenide (CIGS) modules are also subject to light‐induced change of the module efficiency . Research on these module technologies has shown that they may degrade with light exposure, but in some cases, it has been shown that they remain stable or improve . The behaviour is, in general, very dependent on the deposition and exact material composition.…”
Section: Introductionmentioning
confidence: 99%
“…The behaviour is, in general, very dependent on the deposition and exact material composition. In general, these modules exhibit a short‐term meta‐stable behaviour modulated by light, and for this reason, they have to be measured quickly following light exposure .…”
Section: Introductionmentioning
confidence: 99%